HUBUNGAN MEKANISME PENYALURAN PUPUK BERSUBSIDI DENGAN KEBERHASILAN PETANI DALAM ADOPSI TEKNOLOGI PEMUPUKAN DI DESA PURWOASRI KECAMATAN SINGOSARI - Aek, Imelda Rosanti; Asnah, Asnah; Kholil, A. Yusuf (BUANA SAINS, 2024)
This research aimed to determine the relationship between the subsidized fertilizer distribution mechanism and the success of farmers in adopting fertilization technology. This study used a descriptive method approach—data retrieval techniques using interviews, documentation, and observation. The mechanism for distributing subsidized fertilizers in Purwoasri Village, Singosari District  According to the results of the recapitulation of the subsidy fertilizer distribution mechanism, researchers explained that the distribution mechanism and technology adoption with the following percentages: subsidized fertilizer distribution mechanism 74%, the role of agricultural extension workers 76%, the role of farmer groups 79%, meaning that the distribution mechanism has been successfully carried out well, such as extension workers helping and guiding farmers in the preparation of RDKK (Plan Definitive Group Needs). Meanwhile, the adoption of 70% fertilization technology means that extension workers and farmers complement each other and work together to achieve the success of farmers in the successful adoption of fertilization technology in Purwoasri Village.